Hybrid Light‐Emitting Transistors Based on Low‐Temperature Solution‐Processed Metal Oxides and a Charge‐Injecting Interlayer. Issue 2 (19th November 2015) - Ullah, Mujeeb; Lin, Yen‐Hung; Muhieddine, Khalid; Lo, Shih‐Chun; Anthopoulos, Thomas D.; Namdas, Ebinazar B.
Abstract : The performance of solution and low‐temperature processed hybrid light‐emitting field‐effect transistors is enahnced by a new development strategy. The manipulation of the work function at the oxide/polymer interface is presented for achieving high all‐round performance in these devices.